A case of IgG4-related ophthalmic disease after SARS-CoV-2 vaccination: case report and literature review - Zhang, Peixuan; Wu, Qian; Xu, Xiao; Chen, Minliang (Frontiers in Immunology, 2024)
Coronavirus disease 19 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is affecting the world with a surge in cases. A variety of autoimmune diseases occur after SARS-CoV-2 infection or vaccination, of which IgG4-related disease (IgG4-RD) is an important type. IgG4-RD can involve multiple organs of the body. The ocular manifestation of IgG4-RD is called IgG4-related ophthalmic disease (IgG4-ROD). We herein report a patient diagnosed with IgG4-ROD. The patient developed ptosis and vision loss after SARS-CoV-2 vaccination, and